Pengaruh Live Streaming dan Brand Image terhadap Keputusan Pembelian Produk The Originote pada Pengguna Tiktok Shop di Daerah Istimewa Yogyakarta - Dafa Karensha Aripin; Wina Driyan Pradana (Journal of Management and Social Sciences, 2024)
Technological developments make it easier for humans to do all activities online, such as online shopping, so that business people form marketing strategies using live streaming and building brand image. The Originote is one of the skincare products that uses a form of marketing strategy in the form of building a brand image through live streaming. To determine the effect of live streaming and brand image on purchasing decisions for The Originote products for TikTok shop users in the Special Region of Yogyakarta partially or simultaneously. Using a quantitative approach. The research data source comes from primary data obtained by distributing questionnaires to respondents. The data collection technique uses non-probability sampling (purposive sampling). The research sample was 112 respondents with the criteria of having purchased The Originote product at TikTok Shop at least once, being in the Special Region of Yogyakarta and being over 18 years old. The data was processed using SPSS version 27 software. It is found that live streaming has a partial effect on purchasing decisions. Brand image has a partial positive effect on purchasing decisions. Live streaming and brand image simultaneously have a positive effect on purchasing decisions.